Detection of subsurface layers by Sub Bottom Profiling (SBP) of cross section of Shatt Al-Arab River at Al-Rebat branch, Basrah, southern Iraq - Muttashar, W.R.; Al-Mosawi, W.M.; Al-Aesawi , Q.M.; Abas, N.S. (Mesopotamian Journal of Marine Sciences, 2022)
Two types of the subsurface layers were investigated by two Boreholes on the two banks of the Shatt Al Arab River near the old Al-Rebat port at Basrah city. Sub Bottom Profiling along the River section has also been investigated. The boring was carried out in two sides of Shatt Al-Arab at Al-Ashar and Al-Tanuma sides at Al-Rebat square. Marine geophysical investigations were made including Sub Bottom profile technique (SBP) using the Strata Box instrument. Besides, Acoustic Doppler Current Profiler (ADCP) technique was used along a 400 m section for determining the cross section of the River. the Boring Log Data of two Boreholes have been represented depending on SPT Values as the bearing Strength of subsoil layers profiles, which is matching with the sedimentary layers resulting from the seismic profiles for obtaining the geotechnical model of subsurface layers along cross section of the River. High bearing capacity layer is very dense sandy layer which appears at -22m of the elevation on sea level and extends to -29 m in left bank of the River. This layer is old deposits belonging to Dibdiba deposits (upper Miocene-Pleistocene).